Recovering Uniform Coverage in a 3D Survey: Case Study from Onshore Southern India - K. Shukla; P. Jaiswal; C. S. Singh (International Journal of Geophysics)
We present a case study on 3D seismic acquisition under inaccessible ground conditions and heavy head-loads. The novelty in this case study is designing novel shot recovery strategies. The study area is in a densely populated region in Southern India, where a 3D survey was conducted over an area of 700 km2 to illuminate a target formation at 3000 m depth. The survey was designed in a brick pattern with six shots in a round, a line repeat interval of 2, and offset and skid grid of 300 m × 300 m. Only 40% of full fold could be obtained with conventional shot recovery methods. To increase the survey fold, two new shot recovery strategies were attempted. First, the original offset and skid grid was increased to 1100 m × 1200 m. Second, if the recovery shot did not fall in this grid, it was relocated along the swath from its original location to a distance equal to half the inline offset. The two strategies, employed together, increased the fold to 90% of full fold at the target area maintaining its uniformity. Although the illumination of the target zone was adequate for interpretation in this case, we see a need for adaptation if these strategies are to be applied in other surveys. In general, issues related to offset-limit, shot-density, and grid-spacing are a matter of continual optimization in 3D surveys.